Teachers’ Perception of English as Medium of Instruction in Nepalese Community Schools - Panthee, Dinesh (KMC Research Journal, 2020)
English as Medium of Instruction (EMI) has been a burning issue of the pedagogical field among the concerned stakeholders including teachers. The objective of this study was to find out the perception of the community schools’ teachers in shifting the medium of instruction to English in the multilingual classroom contexts. It also aimed to explore the opportunities and challenges of shifting the medium of instruction Nepali to English in community schools. It is a qualitative design with a phenomenological study. The participants of the study were two teachers of a community school of Sainamaina Municipality of Rupandehi who are teaching other than English subjects in English medium. A semi-structured interview technique was used to gather information from the participants. The main finding of the study was that the use of EMI in community schools is beneficial. It is also found that teachers of community schools were positive in implementing EMI in conducting their daily teaching and learning activities even though there are certain challenges like linguistic difficulties, inadequate language abilities of teachers, cultural diversity, less effective pedagogy, limited resources, etc.